2021
DOI: 10.1371/journal.ppat.1009407
|View full text |Cite
|
Sign up to set email alerts
|

A cross-neutralizing antibody between HIV-1 and influenza virus

Abstract: Incessant antigenic evolution enables the persistence and spread of influenza virus in the human population. As the principal target of the immune response, the hemagglutinin (HA) surface antigen on influenza viruses continuously acquires and replaces N-linked glycosylation sites to shield immunogenic protein epitopes using host-derived glycans. Anti-glycan antibodies, such as 2G12, target the HIV-1 envelope protein (Env), which is even more extensively glycosylated and contains under-processed oligomannose-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 92 publications
(93 reference statements)
5
25
1
Order By: Relevance
“…Finally, that FDG Abs can bind multiple glycan clusters and use multiple BCRs, combined with FDG precursors being well represented in human B cell repertoire make this new category of glycan-reactive B cells an attractive target to consider for induction by HIV-1 vaccines. Since the submission of this paper, Lee et al have reported that the FDG Ab 2G12 can neutralize strains of influenza (Lee et al, 2021), further demonstrating the breadth of cross-binding activity of the 2G12 FDG Ab for glycosylated virus pathogens.…”
Section: Llmentioning
confidence: 82%
“…Finally, that FDG Abs can bind multiple glycan clusters and use multiple BCRs, combined with FDG precursors being well represented in human B cell repertoire make this new category of glycan-reactive B cells an attractive target to consider for induction by HIV-1 vaccines. Since the submission of this paper, Lee et al have reported that the FDG Ab 2G12 can neutralize strains of influenza (Lee et al, 2021), further demonstrating the breadth of cross-binding activity of the 2G12 FDG Ab for glycosylated virus pathogens.…”
Section: Llmentioning
confidence: 82%
“…However, surface glycans could also be the target of antibodies and glycan-binding agents. Several broad and potent neutralizing mAbs target the specific glycan of viral surface glycoproteins were identified [ 35–37 ], and glycan-binding proteins such as lectins exhibit antiviral activities [ 11 ]. Although the highly glycosylated SARS-CoV-2 S protein is continuously mutated and antigenic variants resistant to mAbs and vaccine-generated antibodies emerged, the glycosylation sites are conserved so far, which provide a candidate target for anti-SARS-CoV-2 strategy against variants.…”
Section: Discussionmentioning
confidence: 99%
“…Glycan clustering is amplified at the quaternary junctions formed by protein oligomers, such as trimeric viral proteins like SARS-CoV-2 spike protein and Influenza HA. Indeed, Lee et al provide evidence that the 2G12 glycoepitope on Influenza H3N2 is quaternary and neutralizing, though the neutralizing effect may also be driven by the glycoepitope's location proximal to the functionally-important receptor binding site (Lee et al, 2021). The 2G12 topological glycoepitope on SARS-CoV-2 is also quaternary (Acharya et al, 2020).…”
Section: Topological Glycoepitopesmentioning
confidence: 99%
“…However, topological glycoepitopes do not appear unique to HIV, and recent evidence suggests that 2G12 recognizes topological glycoepitopes on additional viruses. At the time of this writing, 2G12 glycoepitopes have been identified on Influenza H3N2 Lee et al (2021) and SARS-CoV-2 ( Acharya et al, 2020 ; Mannar et al, 2021 ).…”
Section: Defining Glycoepitopes On Viral Surfacesmentioning
confidence: 99%